Optimasi Formula Patch Anti Jerawat Dari Ekstrak Batang Pisang Ambon dengan HPMC-Kitosan menggunakan Simplex Lattice Design - Fardanu, Arvian Rifky; Suprapto, Suprapto (Journal of Pharmaceutical and Sciences, 2026)
Acne is a chronic inflammatory skin disease involving sebaceous gland hyperactivity, abnormal follicular keratinization, excessive bacterial colonization, immune response, and inflammation. The main causes include pore obstruction due to excess sebum, with Cutibacterium acnes as the dominant bacteria. Increasing concerns about the side effects of chemical drugs and antibiotic resistance encourage the development of safer and more sustainable natural treatments. Ambon banana stem (Musa paradisiaca var. sapientum) contains bioactive compounds such as tannins, saponins, and flavonoids that exhibit antibacterial, anti-inflammatory, and antioxidant activities. This study aims to optimize the anti-acne patch formula from Ambon banana stem extract using hydroxypropyl methylcellulose (HPMC) and chitosan polymers through simplex lattice design (SLD) in Design-Expert® v.13. Eight formulas were made and evaluated for their physical properties, including weight uniformity, thickness, pH, moisture absorption, folding resistance, and swelling index. The optimal formula was obtained in a combination of 4 g HPMC and 0.5 g chitosan with a desirability value of 0.645. The results of the optimal formula validation with a paired t-test showed no significant differences in the formula except for pH. The Ambon banana tree stem extract patch produced an inhibition zone of 13 ± 0.5 mm against Cutibacterium acnes with a strong category although lower than the pure extract (19.03 mm) and clindamycin control (21.17 mm). This patch offers controlled drug release, ease of use without contamination, and increased patient compliance, making it an effective alternative natural acne treatment.